Association Between Drug Related Problems and Outcomes of Tuberculosis Patients at Citra Husada Hospital Jember - Lutvi Anggraeni; Fifteen Aprila Fajrin; Afifah Machlaurin; Irma Prasetyowati; Angga Mardro Rahardjo (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Background: Tuberculosis (TBC) remains a major global challenge. In Indonesia, the success rate for Drug-Sensitive Pulmonary TB (DS-TBC) treatment is still below target, often linked to Adverse Drug Reaction (ADR) and Drug Related Problem (DRP). The complexity of regimens and polypharmacy increases the risk of DRPs, which are strong predictors of treatment failure. Objective: This study aimed to identify DRPs and analyze their relationship with the clinical outcomes of DS-TBC. Method: A retrospective cohort study was conducted on 281 DS-TBC patients recorded at Citra Husada Hospital Jember from January 2020 to December 2023. Data were collected from medical records and the TBC Information System (SITB). DRPs were identified using the PCNE V9.1 classification, focusing on dose inappropriateness, drug interactions, and ADR. Outcomes were categorized as successful (cured/treatment completed) or unsuccessful. Result: Data analysis included descriptive statistics, bivariate analysis using Chi-Square, and multivariate analysis using Binary Logistic regression with a significance p < 0,05. The result of this study is that patients were predominantly male (55.16%), aged 46-65 years, with a treatment completion rate of 82.21%. DRPs were found in 84.34% of patients, dominated by drug interactions (79%) and ADRs (35.23%), although the accuracy of anti-TB drug dosage was 100%. In multivariate analysis, age ≥65 years was associated with a decreased likelihood of successful treatment (aOR 0.367), while respiratory tract medication administration was associated with an increased likelihood of successful treatment (aOR 2.477). The overall relationship between DRPs and outcome was not statistically significant. Conclusion: Sociodemographic factors (age) and clinical symptom management (respiratory therapy) play the most crucial roles in determining the treatment outcome. Effective pharmaceutical intervention is suggested to mitigate the impact of DRPs on treatment failure. More aggressive clinical management is necessary for elderly patients.